2013
DOI: 10.1002/ps.3470
|View full text |Cite
|
Sign up to set email alerts
|

Cyflumetofen, a novel acaricide – its mode of action and selectivity

Abstract: The mode of action of cyflumetofen is to inhibit mitochondria complex II by affecting its action site after being metabolised to AB-1. However, inhibition by cyflumetofen and AB-1 in other organisms was very weak. Selectivity for other organisms has contributed to differences in action site activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 18 publications
6
81
0
Order By: Relevance
“…Furthermore, our study revealed that pyflubumide-deisobutylated metabolite 9 inhibits electron transport in mitochondrial complex II of spider mites, as with the cases of beta-ketonitrile acaricides. 21,22) However, it was also suggested that their binding sites on mitochondrial complex II and/ or the manners of binding are not identical. 20,23,24) These results demonstrate that pyflubumide could be a promising new acaricide.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our study revealed that pyflubumide-deisobutylated metabolite 9 inhibits electron transport in mitochondrial complex II of spider mites, as with the cases of beta-ketonitrile acaricides. 21,22) However, it was also suggested that their binding sites on mitochondrial complex II and/ or the manners of binding are not identical. 20,23,24) These results demonstrate that pyflubumide could be a promising new acaricide.…”
Section: Resultsmentioning
confidence: 99%
“…Cyflumetofen provides rapid knockdown of spider mites pest through contact activity, typically within 3 hours after application, and has been observed to control mite populations up to 28 days after application [91]. Cyflumetofen and cyenopyrafen both interfere with mitochondrial electron transport, but contrary to METIs (Complex I inhibitors) and bifenazate and acequinocyl (Complex III inhibitors, see section 3.2), these compounds inhibit complex II of mitochondrial electron transport chain [86,93]. Recently it was also reported that both cyenopyrafen and cyflumetofen are pro-acaracides that need bio-activation by hydrolysis [86,93].…”
Section: Novel Complex II Inhibitorsmentioning
confidence: 99%
“…during all life stages, although some highly multi-resistant T. urticae strains might show cross-resistance [85]. Moreover, they do not affect a variety of non-targeted arthropod species [86][87][88][89][90][91] and can be integrated in IPM programs. In addition to its efficacy in spider mite control, cyflumetofen also seems to be a promising tool for effective control of Brevipalpus sp.…”
Section: Novel Complex II Inhibitorsmentioning
confidence: 99%
“…The most recently developed class of acaricides are mitochondrial complex II (succinate-quinone oxidoreductase) inhibitors, such as cyenopyrafen. [10][11][12] For resistance management and effective and sustainable use of these compounds, it is important to execute a resistance-management strategy through rotating acaricides with differing modes of action. 13) Pyflubumide is a novel and potent acaricidal compound that was developed by Nihon Nohyaku Co., Ltd. (R=COCH(CH 3 ) 2 , Fig.…”
Section: Introductionmentioning
confidence: 99%